CONCEPTUALIZING ADVERTISING RESEARCHES OF MEASURING ADVERTISING EFFECTIVENESS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This paper aims to address this gap by providing a comprehensive conceptualization of advertising research that focuses on measuring advertising effectiveness. Drawing on a thorough review of the literature, this paper provides an overview of the concept of advertising effectiveness and the different approaches to measuring it. The paper then explores the various types of advertising research that have been conducted, including qualitative and quantitative research, as well as traditional and digital research methods. The challenges associated with measuring advertising effectiveness, such as the difficulty in establishing causality and the impact of external factors, are also discussed. One key contribution of this paper is the proposal of a framework for conducting effective advertising research, which includes clearly defining research objectives, selecting appropriate research methods, and considering the limitations and potential biases in the research design. The framework is intended to help researchers and practitioners to conduct research that is more effective and efficient in measuring advertising effectiveness. Overall, this paper aims to contribute to the understanding of advertising research by providing acomprehensive and up-to-date overview of the field. It is hoped that the proposed framework will be useful in guiding future research and practice, ultimately leading to more effective and efficient advertising campaigns.